2014
DOI: 10.5539/gjhs.v7n2p80
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Contraception in Adolescents: Data From a Single Tertiary Clinic in Southeast of Turkey

Abstract: Aim:We aimed to evaluate the postpartum contraception preferences of adolescent women in this study.Material and Method:This descriptive study was prepared after a retrospective analysis of file records of primigravida women who had given birth at the Adiyaman University School of Medicine Training and Research Hospital Department of Obstetric and Gynecology between January 2010 and June 2012. More than 12 months had passed after birth. The adolescents who were included in the study and the control group women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
0
7
0
3
Order By: Relevance
“…The study on use of LAM as a family planning method with the most recent data was conducted in Turkey in 2010-2012. 48 It found that 50.6% of those 10-19 years old were using lactational amenorrhoea as a family planning method compared with 33% among women 20-35 years. 48 LAM was the most preferred method of contraception in this study (no quantitative indicators were provided to support this statement).…”
Section: Theme 1: Duration and Outcomes Of Postpartum Or Lactational mentioning
confidence: 99%
See 1 more Smart Citation
“…The study on use of LAM as a family planning method with the most recent data was conducted in Turkey in 2010-2012. 48 It found that 50.6% of those 10-19 years old were using lactational amenorrhoea as a family planning method compared with 33% among women 20-35 years. 48 LAM was the most preferred method of contraception in this study (no quantitative indicators were provided to support this statement).…”
Section: Theme 1: Duration and Outcomes Of Postpartum Or Lactational mentioning
confidence: 99%
“…48 It found that 50.6% of those 10-19 years old were using lactational amenorrhoea as a family planning method compared with 33% among women 20-35 years. 48 LAM was the most preferred method of contraception in this study (no quantitative indicators were provided to support this statement). 48 Contraceptive failure in the adolescent age group was 2.37% in the first year post partum (12 unintended pregnancies among 506 adolescents in sample), compared with 2.0% in older age group.…”
Section: Theme 1: Duration and Outcomes Of Postpartum Or Lactational mentioning
confidence: 99%
“…Adolesan yaş grubu gebelerin yaş ortalaması 17.12±1.07(14-18), ileri yaş grubu gebelerin yaş ortalaması 41.46±2.16(39-50) kontrol grubunun yaş ortalaması 28.88±6.02 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), olarak saptandı. Adolesan yaş gebelerin büyük çoğunluğu nullipar (1-3) iken ileri yaş gebelerin tamamı multipar (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) idi. Gravida açısından değerlendirildiğinde en yüksek değer ileri yaş grubunda olduğu gözlendi.…”
Section: Bulgularunclassified
“…Hospitalizasyon süresi en uzun ileri yaş grubu gebelerde izlendi. Adolesan ve reprudüktif yaş grubu gebelerde adolesan yaş gebelerin büyük çoğunluğu nullipar (1-3) iken ileri yaş gebelerin tamamı multipar (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) idi. 1.ve 5.Apgar skorları açısından gruplar arasında anlamlı bir farklılık saptanmadı (p=0.077, p=0.087).…”
Section: Bulgularunclassified
See 1 more Smart Citation